Correction: CXCR3 chemokine receptor contributes to specific CD8+ T cell activation by pDC during infection with intracellular pathogens. - Camila Pontes Ferreira; Leonardo Moro Cariste; Isaú Henrique Noronha; Danielle Fernandes Durso; Joseli Lannes-Vieira; Karina Ramalho Bortoluci; Daniel Araki Ribeiro; Douglas Golenbock; Ricardo Tostes Gazzinelli; José Ronnie Carvalho de Vasconcelos (PLoS Neglected Tropical Diseases)
[This corrects the article DOI: 10.1371/journal.pntd.0008414.].